Plano de segurança da água para consumo humano em comunidade rural - Steffler, Tainara Luana Schmidt (2023)
The growing demand in terms of safety for the water quality available for human consumption raises the need for the elaboration and implementation of a viable and safe preventive instrument for water management. The Water Safety Plan is an extremely important tool for public supply planning and is intended to provide a service that integrates basic sanitation safely with the quality and health of the population. The research aimed to develop the Water Safety Plan – WSP in a water supply system for human consumption in the community of Lajeado Fortuna in the municipality of Tenente Portela/RS, which includes the identification of hazards and dangerous events, the characterization of risks, establishment of control measures and improvement plans in all stages that make up the system, from water collection to the final consumer, including intra-household installations, taking into account all the particularities of the integrated system. The methodology composes the field data survey with the description of the WSS and use of software to fill in the prioritization matrix and risk classification. Sixty six dangerous events were identified, mainly related to the watershed stages and the home environment. It is worth highlighting the precariousness of rural sanitation, which implies the proposal of control measures and a schedule of short-term actions to reduce and eliminate the risks that are affecting the water security of the community supplied. The research made it possible to obtain subsidies for the implementation of the WSP in any WSS, making it possible to adapt the evaluation methodology to the reality of each location.